Improving Quality of Life of the Elderly with Hypertension by Family Support - Iswatun, Iswatun; Efendi, Ferry; Umam, Khotibul; Susanto, Joko; Indira Murty, Maulida; Hidaayah, Nur; Rukanah, Rukanah (Jurnal MIDPRO, 2023)
Quality of life can affect the life of everyone, including the elderly. The elderly are people who live in a continuous aging process, which is manifested by decreased immunity or is susceptible to various diseases that can cause death. The purpose of this study was to analyze the relationship between family support and quality of life in the elderly with hypertension at the Parengan Tuban Health Center. The design of this study uses correlational analytic with a cross-sectional approach. The number of samples is 144, using purposive sampling technique. The inclusion criteria for this study were the elderly with hypertension, the elderly were conscious, the elderly were in a good cognitive state, the elderly were able to communicate, and the elderly were willing to be respondents. The research instrument was a family support questionnaire, and an Older People Quality Of Life-Brief questionnaire. The data were analyzed using the Sperman Rank (Rho) statistical test with a significance <0.05. The results showed that most of the family support was good at 70.8% and the quality of life was very good 69.4% and the result of the p-value test was 0.01, meaning that there is a relationship between family support and the quality of life of the elderly with hypertension. This research is expected to have implications for family empowerment in the form of increasing family support that can improve the quality of life in the elderly with hypertension.